Dampak Media Sosial, Keputusan Pembelian Impulsif, dan Implikasi Pembelian Impulsif terhadap Keuangan Pribadi Generasi Z (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of social media usage and impulsive purchasing decisions on personal financial management of Generation Z in Indonesia. In the digital era, social media has become an integral part of Generation Z lives, influencing their consumer behavior, including triggering impulse purchases. Uncontrolled impulsive buying can have a negative impact on financial health. This study uses a quantitative descriptive approach, with primary data collected through questionnaires distributed to 68 Generation Z respondents in Indonesia. The results of the study show that: (1) The use of social media has a positive and significant effect on personal financial management of Generation Z (t count 2.586 > t table 1.668; sig. 0.012 < 0.05) . (2) Impulsive purchasing decisions have a positive and significant influence on Generation Z personal financial management (t count 3.129 > t table 1.668; sig. 0.003 < 0.05). (3) Simultaneously, the use of social media and impulsive purchasing decisions have a significant influence on Generation Z personal financial management (F count 5.108 > F table 3.14; sig. 0.009 < 0.05). In conclusion, both social media and impulsive buying together have a significant influence on Generation Z financial management.